2012
DOI: 10.1097/mpg.0b013e318262de16
|View full text |Cite
|
Sign up to set email alerts
|

Improved Outcomes With Quality Improvement Interventions in Pediatric Inflammatory Bowel Disease

Abstract: Our results show that significant improvements in patient outcomes are associated with QI efforts that do not rely on new medication or therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 52 publications
0
26
0
2
Order By: Relevance
“…We were not able to perform a similar analysis for fecal calprotectin in our cohort given the small number of patients with the biomarker collected, but studies have shown that a fecal calprotectin >400 mcg/gm in those with clinically quiescent IBD is associated with increased risk of disease relapse in the following year. 44,45 …”
Section: Discussionmentioning
confidence: 99%
“…We were not able to perform a similar analysis for fecal calprotectin in our cohort given the small number of patients with the biomarker collected, but studies have shown that a fecal calprotectin >400 mcg/gm in those with clinically quiescent IBD is associated with increased risk of disease relapse in the following year. 44,45 …”
Section: Discussionmentioning
confidence: 99%
“…56 Children with low vitamin D levels are more likely to have disease recurrence, and maintaining serum vitamin D levels greater than 30 ng/mL increases the likelihood of maintaining clinical remission. 57 …”
Section: Long-term Sequelaementioning
confidence: 99%
“…Optimization of vitamin D and calcium delivery is advisable as this may theoretically help decrease deficits in BMD—though it should be noted that treatment with vitamin D has not been shown to improve BMD in CD (69). The North American Society of Pediatric Gastroenterology Hepatology and Nutrition recommends yearly screening of vitamin D (in the spring) and treating levels <20 with courses such as 50,000 IU vitamin D /week x 6 weeks (70, 71). …”
Section: Prevention and Treatment Of Endocrine Co-morbiditiesmentioning
confidence: 99%
“…Close monitoring of disease symptomatology and testing of intestinal inflammation via measurement of fecal calprotectin may assist in diagnosis of occult increases in disease activity (71). Additional steps targeting puberty and growth can be added should disease severity and endocrine sequelae persist despite escalation in CD-specific treatment.…”
Section: Prevention and Treatment Of Endocrine Co-morbiditiesmentioning
confidence: 99%